Transformasi Menuju Madrasah Bermutu Terpadu - Novan Ardy Wiyani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract:The growth of madrasah in Indonesian homeland is the result of pull of the pesantren as native Indonesian educational institutions (conventional) that are already on one side with a western education (modern) on the other. In the colonial period, in accordance with the mission of colonialism, madrasah are so marginalized and made a variety of colonial government policies that marginalize the madrasah. One impact is still visible from the discriminatory policy is madrasah experienced a variety of management weaknesses. Under these circumstances, management weaknesses indicated by the closed nature and is not oriented to the outside so that the madrasah was a slow progression and even static. To overcome this, one of the rescue efforts that can be taken by the stakeholders of education in the madrasah is to change the paradigm of conventional management on the quality of madrasah into an integrated paradigm. This paper describes the transformation towards integrated quality of madrasah. The author conducted an analysis of integrated quality management theory and then demonstrate its application in the field of Islamic education can do madrasah to get a quality education services. Key words: Grow of madrasah anf integrated quality management.